System for real-time signal processing - Azpiroz Leehan, J.; Linding Boes, M. (Revista Mexicana de Ingenieria Biomedica, 2018)
A coprocessor capable of converting an IBM-type personal computer into a biomedical signal processing system in real time is described. Its design philosophy and the essential components of this system are explained. The applications of it are mentioned.